Osthole Attenuates Macrophage Activation in Experimental Asthma by Inhibitingthe NF-ĸB/MIF Signaling Pathway - Li, Ruyi; Song, Peng; Tang, Guofang; Wei, Jianghong; Rao, Lizong; Ma, Libing; Jiang, Ming; Huang, Jianwei; Xu, Qing; Wu, Jingjie; Lv, Qian; Yao, Dong; et al. (Frontiers in Pharmacology, 2021)
Inhibition of activated macrophages is an alternative therapeutic strategy for asthma. We investigated whether a coumarin compound, osthole, isolated from Cnidiummonnieri (L.) Cuss, alleviated macrophage activation in vivo and in vitro. Osthole could reduce expression of a marker of activated macrophages, cluster of differentiation (CD)206, in an ovalbumin-challenge model of asthma in mice. Osthole could also inhibit infiltration of inflammatory cells, collagen deposition and production of proinflammatory cytokines [interleukin (IL)-1β, tumor necrosis factor-ɑ, macrophage migration inhibitory factor (MIF)] in asthmatic mice. In vitro, expression of phosphorylated-IĸBɑ, MIF and M2 cytokines (Ym-1, Fizz-1, arginase-1) in IL-4-induced macrophages decreased upon exposure to the NF-ĸB inhibitor MG-132. In our short hairpin (sh)RNA-MIF-knockdown model, reduced expression of M2 cytokines was detected in the IL-4 + shRNA-MIF group. Osthole could attenuate the proliferation and migration of an IL-4-induced rat alveolar macrophages line (NR8383). Osthole could reduce IL-4-induced translocation of nuclear factor-kappa B (NF-ĸB) in NR8383 cells. Collectively, our results suggest that osthole ameliorates macrophage activation in asthma by suppressing the NF-ĸB/MIF signaling pathway, and might be a potential agent for treating asthma.